VOC Emissions from a Rendering Plant and Evaluation for Removal of Pentanal by Oxidization Using Hydrogen Peroxide - Wen-Hsi Cheng; Chun-Hung Lin; Chung-Shin Yuan; Ken-Lin Chang (Aerosol and Air Quality Research)
Abstract Rendering plants treat dead livestock and produce grease and bone meal. In a rendering plant, the cooking and drying processes are the main sources of odor emissions. Non-fresh dead livestock reduce the performance of odor control devices, and in Taiwan, t he treatment facilities in a rendering plant mostly are operated in a batch feeding, which causes volatile organic compound (VOC) emissions in the exhausted gas, that always caused complaints from the nearby neighborhood. This study used respectively ozone and hydrogen peroxide to evaluate the removal efficiencies of pentanal, hexanal and toluene those are common VOCs in the rendering exhaustion. Experimental results indicated that ozone could not effectively reduce aldehydes and toluene, and the residual ozone remaining in the exhaust gas is a secondary air pollutant and irritate the human respiratory tracts. Oppositely, hydrogen peroxide effectively removed pentanal as a feasible VOC treatment oxidant by adding into a contact reactor. When the pentanal exhaustion concentration from the rendering process was around 36.23 ppm in the flue with the flow rates from 100 to 250 Nm3 min−1, the reaction rate constant of pentanal for the first-order reaction by aqueous hydrogen peroxide of 1,000 mg L−1 was obtained as 0.536 1 s−1, and then the pentanal reduced to 0.68 to 2 ppm. Based on the simulation using the Gaussian dispersion model, the concentration ranges of pentanal in the exhausted stream resulted in the pentanal emission rate lower than 0.01 g s−1, which no longer causes surrounding residents’ complaints.